2017
DOI: 10.2147/ott.s135013
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance therapy with all-trans retinoic acid and arsenic trioxide improves relapse-free survival in adults with low- to intermediate-risk acute promyelocytic leukemia who have achieved complete remission after consolidation therapy

Abstract: BackgroundCurrently, the optimal maintenance therapy for patients with acute promyelocytic leukemia (APL) who have achieved complete remission (CR) after completing consolidation chemotherapy remains controversial. The comparative effectiveness of the all-trans retinoic acid (ATRA) plus arsenic trioxide (As2O3) maintenance strategy with classic ATRA plus chemotherapy has not been evaluated. In this study, we compared the efficacy and toxicity of maintenance therapy with ATRA plus As2O3 and classic ATRA plus ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Considering this, it was not surprising that subsequent studies found that APL patients cured by ATRA treatment relapsed at a median of 3.5 months after achieving remission 27 , 28 . Numerous studies demonstrated the combined ATRA with arsenic regimens drastically reduced relapse in adult patients with APL compared to ATRA treatments without arsenic 29 31 . We demonstrated that p11 and p36 protein levels are stimulated by the expression of the PML/RARα oncoprotein, and ATRA treatment of the APL cell line, NB4, results in the loss of p11 and p36 protein levels 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering this, it was not surprising that subsequent studies found that APL patients cured by ATRA treatment relapsed at a median of 3.5 months after achieving remission 27 , 28 . Numerous studies demonstrated the combined ATRA with arsenic regimens drastically reduced relapse in adult patients with APL compared to ATRA treatments without arsenic 29 31 . We demonstrated that p11 and p36 protein levels are stimulated by the expression of the PML/RARα oncoprotein, and ATRA treatment of the APL cell line, NB4, results in the loss of p11 and p36 protein levels 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with newly diagnosed APL, also known as a AML M3 subtype with APL-specific chromosomal translocation t(15;17) (q22;q21) and PML/RARα chimeric fusion protein, are mostly cured after standard ATRA with chemotherapy, while toxicity and refractoriness to the treatment are observed in some patients. Accumulating evidence shows the superiority of novel combined ATRA and ATO therapy for the treatment of patients with APL in terms of event-free survival, relapse-free survival, and less hematologic toxicity, compared to ATRA with chemotherapy [4,5,[69][70][71][72]. The molecular basis underlying synergistic effects between ATRA and ATO has been biologically demonstrated.…”
Section: Acute Promyelocytic Leukemia (Apl)mentioning
confidence: 99%
“…It has contributed to long term durable remissions and cures in other hematological diseases, such as acute lymphoblastic leukemia and follicular lymphoma, but its role in AML is still controversial. With the exception of arsenic trioxide and retinoic acid in acute promyelocytic leukemia, no maintenance therapy has demonstrated sufficient efficacy to be considered standard in the treatment of AML. The concept of maintenance therapy in AML is based on the premise that the induction therapies currently used are not able to ensure the complete elimination of the leukemic clone.…”
Section: Introductionmentioning
confidence: 99%